ORGANIZATION OF STUDENTS' EDUCATIONAL WORK TECHNICAL UNIVERSITIES (Pedagogy of Higher and Secondary Education, 2006)
In the article some ways of further perfection of technical universities’ students’ educational work taking into consideration new conditions of education are discussed.